Optimization of the leaching process of the printed circuit boards production’s sludge for copper recovery via electrolysis - Thu Huyen, Nguyen Thi; Dung, Dang Trung; Giang, Nguyen Huong; Binh Thanh, Nguyen Dang; Tung, Mai Thanh; Bich Thuy, Hoang Thi (Vietnam Journal of Chemistry, 2017)
Copper is the main component of printed circuit boards (PCBs) which is the main part of an electronic device. The manufacture of PCBs often releases huge amount of sludge which contained copper. Derived from the demand of the industrial park about the wasted sludge treatment and the reducing of the plantation of natural mineral resources, the copper recovery process from PCBs manufacture’s wasted sludge was studied. The process of copper leaching by sulfuric acid solution was studied using experimental planning methods using the simulation software Modde 5.0. The parameters were calculated and simulated to evaluate the effect of the acid concentration, leaching time, and the ratio between the solid and liquid phases on the leaching efficiency. The obtained results by simulation were compared with real experimental results. The obtained results from this study are planning in the actual deployment of the Hanoi Urban Environment One Member Limited Company in Vietnam. Keywords. Printed circuit board, copper sludge, leaching.